Synthesizing the impacts of information and communication technology advancement and educational developments on environmental sustainability: A comparative analyses of three economic blocs—BRICS, MINT, and G7 economies. (21st September 2022) - Gyamfi, Bright Akwasi; Onifade, Stephen Taiwo; Ofori, Elvis Kwame
Abstract: In the wake of the growing threats to humanity from climate change, we analyzed the information and communications technology (ICT)/education—environmental nexus from three distinct blocs including BRICS, MINT, and the G7 economies between 1990 and 2020. Two models were examined to reach the study's objectives. The first model evaluates whether education and ICT are essential for environmental sustainability via potential reduction in carbon emission. On the other hand, the second model fills an existing gap in extant studies by examining the prospect of education and ICT in influencing citizens on the importance of transition to renewable energy usage. Driscoll and Kraay estimator was employed as a panacea tool for cross‐sectional dependence and slope homogeneity while the fixed effect approach provides sufficient robustness checks on the findings. While some outcomes vary per bloc, others are relatively similar across the three blocs. Education level in school enrollment perspectives shows a negative significant pollution reduction effect across the three blocs, while only the G7 bloc performed better from human capital perspectives. The combined sample bloc shows that ICT also significantly reduces carbon emission, however, an individual bloc analysis refutes this stance for the MINT bloc. Additionally, while renewable energy cushions emissions in all the blocs, rapid urbanization, shows a positive CO2 emission impact except in the G7 bloc. Last, ICT and education significantly boost renewable energy usage only in the G7. Hence, governments and stakeholders in the blocs should gravitate toward greater investments in quality education and greener ICT infrastructures for a sustainable environment.